Влияние природы органических реагентов на синтез магнетита - Мицюк, Б.М.; Гузь, Н.В.; Куц, В.А. (Мінералогічний журнал, 2011)
Разработан новый метод синтеза магнетита в процессе органотермальной обработки гематита в присутствии
органических реагентов разной природы (бензол, толуол, гексан, этиловый спирт, ацетон, уксусная кислота,
амид муравьиной кислоты). Показано, что оптимальная для фазового превращения гематита в магнетит в присутствии бензола температура — 450—500, для ледяной уксусной кислоты — 300—340 ºC, в водосодержащих
растворах этилового спирта она составляет 300—340, в растворах ацетона — 340—400 ºC. Установлено, что наличие воды в реакционной среде не влияет на температуру фазового перехода гематит — магнетит. Обнаружено,
что магнетит успешно образуется также при органотермальной обработке вюстита в бензоле. Розроблено новий метод синтезу магнетиту в процесі
органотермальної обробки гематиту в присутності органічних реагентів різної природи (бензол, толуол, гексан, етиловий спирт, ацетон, оцтова кислота, амід мурашиної кислоти). Показано, що оптимальною для
фазового перетворення гематиту в магнетит у присутності бензолу є температура 450—500, для льодяної
оцтової кислоти — 300—340 ºC, у водовмісних розчинах етилового спирту — 300—340, в розчинах ацетону — 340—400 ºC. Встановлено, що присутність води
в реакційному середовищі не впливає на температуру фазового переходу гематит — магнетит. Виявлено, що
магнетит успішно утворюється також внаслідок органотермальної обробки вюститу в бензолі. The authors have developed a new method of magnetite
synthesis in the process of organo-thermal treatment of
hematite in the presence of various organic reagents such
as benzene, toluene, hexane, ethanol, acetone, acetic acid
and amido-formic acid, and determined the optimum
physico-chemical conditions of magnetite phase-pure microcrystals
synthesis with the dimensions similar to those
of the initial hematite crystals (1—5 μm).
The optimal temperature for hematite — magnetite
phase transformation under water-free organo-thermal
conditions in the presence of benzene is 450—500 ºC and
of glacial acetic acid is 300—340 ºC. In water-containing
ethanol solutions, the optimal temperature is 300—340 ºC
and in acetone solutions — 340—400 ºC. Presence of
sufficiently large amounts of water (about 30 and 50 % mixed
with acetone) in the reaction medium does not in fluence
the temperature of hematite — magnetite phase transformation.
Consequently, the main condition of successful
synthesis of magnetite is the presence of organic reagents — reducers of ferric iron ions in the hematite structure.
It was also determined that magnetite is successfully
formed in the process of organo-thermal treatment of
wustite benzene containing ferrous ions. It indicates that
under the experimental conditions, the oxid-redox
equilibrium is established promoting partial oxidation of
ferrous ions and formation of the magnetite structure.